2013
DOI: 10.1016/j.eats.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Outlet Biceps Tenodesis: A New Technique for Treatment of Biceps Long Head Tendon Injury

Abstract: Degeneration and tearing of the long head of the biceps brachii tendon (LHBT) are common intra-articular findings, and surgical intervention including tenodesis or tenotomy is beneficial. A new arthroscopic shoulder technique may be performed through an anterior portal while one is viewing from a posterior portal: (1) Visualize the intra-articular biceps tendon. (2) (7) Identify and cut the remaining stump of the biceps tendon. Seventeen cadaveric shoulders were used to compare the pullout force, stiffness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Autotenodesis of the LHB after tenotomy in the bicipital groove and failure of the tenodesis could be the explanation for these phenomena [8]. Lemos et al [12] have reported a novel technique for treatment of LHB pathology in which a modulated enlarged tendon remains in the bicipital groove after tenotomy. This might reduce the cramping pain and Popeye deformity seen after tenotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Autotenodesis of the LHB after tenotomy in the bicipital groove and failure of the tenodesis could be the explanation for these phenomena [8]. Lemos et al [12] have reported a novel technique for treatment of LHB pathology in which a modulated enlarged tendon remains in the bicipital groove after tenotomy. This might reduce the cramping pain and Popeye deformity seen after tenotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that disclosed the performance profile of RF usage in the shoulder were further analyzed. These studies were grouped by temperature profile (Table 4) [3,20,[52][53][54][55][56][57][58][59][60][61][62] and complications (Table 5) [21,[63][64][65][66][67][68].…”
Section: Performance Profilementioning
confidence: 99%